Reference values for acid-base parameters in healthy mules at high altitude - Vanegas Rincón, Johanna Patricia (2021)
Reference intervals (RI) of physiological parameters related to the acid-base equilibrium state were estimated from blood samples of 76 healthy mules at high altitude. The animals were at rest and subjected to the same diet. The data obtained were compared with those reported by various authors, finding closeness between the estimated RIs and those of the cited authors. It was concluded that the RI of mules and horses do not present great differences.